Medvid E.N. Mass media snfluenceof the interlinguistic and iintralinguistic dynamics - Medvid E. N. (Philological Treatises, 2020)
The article touches upon the problems of mass media influence on language functioning. Being one of the main speech spheres mass media identify the character and peculiarities of any language. The scientific analysis of this process is extrapolated in the notion of “mass media language” the can faster then any other strata of language get into the functioning shifting both at the interlinguistic and intralinguistic levels taking into account the general linguacultural situation in the world.